Prosociality in aging: The contribution of traits and empathic concern. (July 2021) - Cavallini, Elena; Rosi, Alessia; Ceccato, Irene; Ronchi, Luca; Lecce, Serena
Abstract: Past literature on prosocial behavior in aging has mainly focused on age-related differences. However, the analysis of the predictors of prosociality in late adulthood is still under investigated. The present study examines how personality traits predict actual and self-reported prosocial behaviors, while considering the mediation effects of empathic concern and the moderator effect of age, in an Italian sample of 150 participants aged from 55 to 86 years old (Mage = 69.52). Based on a path analysis model, results revealed that agreeableness has a direct association with self-reported prosocial behavior and an indirect relationship, via empathic concern, with actual prosocial behavior. In addition, emotional stability further explains variations in older adults' prosociality, via empathic concern. Age also plays a different role on actual and self-reported behaviors. While the relationship between empathic concern and actual behavior is the same in middle-aged and older adults, in the self-reported behaviors it changes according to the age of participants. As they grow older, people perform prosocial acts in daily life driven by basic dispositions, such as agreeableness, and not by empathic concern. These findings have important implications regarding the understanding of the motives that drive the different prosocial behaviors in the older population.